To compare the effects of multiple sessions of Hyperbaric Oxygen Therapy in neurological improvement in head injury patients: A prospective randomized trial - Yadav, Amlendu; Pawar, Mridula; Garg, Rakesh; Banerjee, Neerja (Journal of Neuroanaesthesiology and Critical Care, 2015)
Introduction: Hyperbaric oxygen therapy (HBOT) is used to improve functional outcome following brain injuries. Different number of sessions of HBOT have been reported but the frequency of HBOT sessions in head injured patients has not been standardized. We planned this prospective randomized study with an aim to compare the neurological effects of 10, 20 and 30 sessions of HBOT in the head injured patients. Materials and Methods: After review board approval, this study was conducted in 60 head injury patients with Glasgow Coma Scale (GCS) score ≤ 9. All patients were resuscitated, stabilized and received neurological care according to institutional protocol. Patients were randomly allotted to–Group H10 (n-20)–which received 10 sittings of HBOT, Group H20 (n-20)–which received 20 sittings of HBOT, Group H30 (n-30)–which received 30 sittings of HBOT. GCS score was recorded after every 10 sittings and at 30 days from initiation of HBOT. Improvement Global rating and Glasgow outcome scale (GOS) were recorded after 30 days. Results: The maximum improvement in GCS scores was seen in group H30. The difference in the average improvement global rating scale was significant between group H10 and group H20, between group H10 and group H30 but was comparable between groups H20 and H30. The GOS was better after 30 sessions as compared to 10 sessions. Patients of all groups showed improvement in spasticity but group H30 showed a maximum improvement. Conclusion: A minimum of 30 HBOT sessions should be considered in head injury patients to show improvement with HBOT. Progressive improvement in GCS scores, GOS, spasticity, mood swings was better seen with increased number of HBOT sessions.
Keywords: Glasgow Coma Scale score; head injury; hyperbaric oxygen therapy; neurological improvement